T177. CANNABIDIOL AS A POTENTIAL PREVENTATIVE TREATMENT IN A NEUREGULIN-1 MOUSE MODEL OF SCHIZOPHRENIA. (18th May 2020) - Visini, Gabriela; Chesworth, Rose; Karl, Tim
Abstract: Background: Schizophrenia is caused by interactions between genes of predisposition and environmental insults. The main pharmacological treatments for schizophrenia are antipsychotic drugs; however, these are associated with a range of side effects (weight gain, metabolic disease, diabetes), have limited treatment compliance, and do not work for approximately 30% of patients. Cannabidiol (CBD) is a non-psychoactive cannabinoid that has shown promise as an antipsychotic-like drug in both human and rodent studies, however its potential as a preventative drug via anti-inflammatory pathways has not yet been investigated. Brain maturation during adolescent development creates a window where CBD could potentially reverse later behavioural deficits via pathways such as anti-inflammation, and reverse the deficits caused by Δ⁹-tetrahydrocannabinol (THC), a psychoactive compound of the cannabis plant linked to the development of schizophrenia. Here we investigated the therapeutic potential of CBD administered in adolescence to protect against the development of schizophrenia-like behaviours, as well as whether CBD could protect against later sensitivity to THC. For this study we used a well-established genetic mouse model of schizophrenia (Nrg1 TM HET) that shows face, construct, and predictive validity for schizophrenia, and is also more susceptible to the effects of cannabinoids. Methods: In this study, male Nrg1 TM HET mice and wild type (WT) mice were treated with 30 mg/kg of CBD or vehicle intraperitoneally for three weeks during adolescence (PND 35–60). Mice were tested CBD-free in adulthood (5–6 mo) in the open field task, which measures locomotion and anxiety (related to positive symptoms in schizophrenia); social interaction, which measures mouse interactions (relevant to negative symptoms); pre-pulse inhibition (PPI), which measures sensorimotor gating (deficits also found in schizophrenia patients); and fear conditioning, which measures associative learning and memory. Mice were then treated after one week washout with either 3 mg/kg of THC or vehicle, and run in a battery of open field, social interaction, and PPI tests. Brains and bloods were collected to investigate neuroinflammation after another week of washout. Western blots were used to investigate Iba1 levels, while ELISA was used to investigate levels of cytokines IL-10, IL-1B, and TNF-a. Results: CBD treatment significantly reduced anxiety in Nrg1 TM HET mice but not WT mice, however it had no effect on locomotion in either group in the open field task. CBD treatment lowered the frequency of total social interaction in both genotypes, and reduced the frequency of social interactions of Nrg1 TM HET to WT levels. CBD reduced PPI in Nrg1 TM HET mice but not WT mice, and Nrg1 TM HET mice had lower overall PPI than WT mice. There was no effect of CBD on fear-associated memory. CBD effects on THC sensitivity in these mice are ongoing, as are brain cytokine and protein analyses. Discussion: These results suggest that Nrg1 TM HET mice are more susceptible to the effects of chronic CBD in adolescence, despite a significant washout. This confirms previous data from our laboratory demonstrating increased susceptibility of Nrg1 TM HET male mice to cannabinoid constituents, and suggests persistent brain changes following adolescent exposure to CBD. Potential reasons for these persistent changes include an altered neuroinflammatory profile in Nrg1 TM HET mice. CBD has previously been shown to be anxiolytic in other studies and our results confirm its potential as an anxiolytic, particularly in our model of schizophrenia.